The Threat of Shop Tokopedia in the Practice of Trade Monopoly and Unfair Business Competition Against the Sustainability of MSMEs in Bukittinggi City - Aziz, Febrian Al (University of Merdeka Malang, 2024)
The purpose of this study is to examine the impact and threat of monopolistic practices and unfair business competition in Shop Tokopedia on the sustainability of MSMEs in Bukittinggi City. Along with the rapid development of the era of globalization and technology, more and more business actors are competing to improve their respective living standards, without regard to healthy business competition. This research uses a qualitative research approach, namely conducting a research process by understanding the phenomenon of business competition that occurs in Shop Tokopedia by creating a comprehensive and complex picture, reporting detailed views obtained from informant sources and based on legal theories, and carried out in a natural setting. The existence of Law Number 5 Year 1999 is a form of government concern to protect and provide justice for business actors in Indonesia. On the other hand, the government also needs to review the Implementation of Law Number 5 Year 1999 in the field has not been able to guarantee and fulfill a sense of justice for the sustainability of MSMEs in order to avoid monopolistic practices and unfair business competition.